Long‐read nanopore sequencing resolves a TMEM231 gene conversion event causing Meckel–Gruber syndrome. Issue 2 (11th November 2019) - Watson, Christopher M.; Dean, Philip; Camm, Nick; Bates, Jennifer; Carr, Ian M.; Gardiner, Carol A.; Bonthron, David T.
Abstract: The diagnostic deployment of massively parallel short‐read next‐generation sequencing (NGS) has greatly improved genetic test availability, speed, and diagnostic yield, particularly for rare inherited disorders. Nonetheless, diagnostic approaches based on short‐read sequencing have a poor ability to accurately detect gene conversion events. We report on the genetic analysis of a family in which 3 fetuses had clinical features consistent with the autosomal recessive disorder Meckel–Gruber syndrome (MKS). Targeted NGS of 29 known MKS‐associated genes revealed a heterozygous TMEM231 splice donor variant c.929+1A>G. Comparative read‐depth analysis, performed to identify a second pathogenic allele, revealed an apparent heterozygous deletion of TMEM231 exon 4. To verify this result we performed single‐molecule long‐read sequencing of a long‐range polymerase chain reaction product spanning this locus. We identified four missense variants that were absent from the short‐read dataset due to the preferential mapping of variant‐containing reads to a downstream TMEM231 pseudogene. Consistent with the parental segregation analysis, we demonstrate that the single‐molecule long reads could be used to show that the variants are arranged in trans . Our experience shows that robust validation of apparent dosage variants remains essential to avoid the pitfalls of short‐read sequencing and that new third‐generation long‐read sequencing technologies can already aid routine clinical care.